The impact of altered polyprotein ratios on the assembly and infectivity of Mason-Pfizer monkey virus - Kohoutová, Zdena; Rumlová, Michaela; Andreánsky, Martin; Sakalian, Michael; Hunter, Eric; Pichová, Iva; Ruml, Tomáš (Virology, 2009)
Most retroviruses employ a frameshift mechanism during polyprotein synthesis to balance appropriate ratios of structural proteins and enzymes. To investigate the requirements for individual precursors in retrovirus assembly, we modified the polyprotein repertoire of Mason-Pfizer monkey virus (M-PMV) by mutating the frameshift sites to imitate the polyprotein organization of Rous sarcoma virus (Gag-Pro and Gag-Pro-Pol) or Human immunodeficiency virus (Gag and Gag-Pro-Pol). For the "Rous-like" virus, assembly was impaired with no incorporation of Gag-Pro-Pol into particles and for the "HIV-like" virus an altered morphogenesis was observed. A mutant expressing Gag and Gag-Pro polyproteins and lacking Gag-Pro-Pol assembled intracellular particles at a level similar to the wild-type. Gag-Pro-Pol polyprotein alone neither formed immature particles nor processed the precursor. All the mutants were non-infectious except the "HIV-like", which retained fractional infectivity.
Keywords: COS Cells; Frameshift Mutation; Mason-Pfizer monkey virus; Humans; Gene Products, gag; zvířata; RNA virová; virion; Financing, Organized; messenger RNA; virové proteiny; financování organizované; AIDS opičí; RNA, Viral; Gene Products, pol; COS buňky; Rous sarcoma virus; Viral Proteins; virus Rousova sarkomu; Chlorocebus aethiops; transfekce; Transfection; posunová mutace; Animals; Protein Biosynthesis; RNA, Messenger; lidé; Masonův-Pfizerův opičí virus; proteosyntéza; genové produkty pol; genové produkty gag; Virion; Cercopithecus aethiops; Simian Acquired Immunodeficiency Syndrome